ANALISIS PROGRAM KEMITRAAN CSR PT. TELEKOMUNIKASI INDONESIA DALAM UPAYA PENINGKATAN KINERJA UMKM (Studi Pada UMKM Mitra Binaan PT. Telkom Witel Semarang) - Christina Dessy Permatasari; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2021)
Abstract: PT. Telkom is one of the state-owned companies trying to build trust by using the strategy of developing CSR programs. Telkom has also thought about no longer working solely to get the maximum profit, but is more inclined towards building long-term business sustainability and empowering the community (community development). Based on interviews with the staff of the CDC Unit PT. Telkom Witel Semarang, the results of the evaluation of MSMEs Andjani and Wingko "O" in the report on the installment report for the repayment of loan funds for the Telkom Witel Semarang Partnership Program, are included in the current category. However, this does not adequately describe the performance of these foster partners experiencing development or improvement. This opinion is strengthened by a statement (Tambunan, 2012) regarding business development which is influenced by capital, marketing, raw materials, labor, technology, transportation costs, high energy, communication, and administrative procedures.This study aims to analyze the extent to which the implementation of the CSR Partnership Program of PT. Telkom by comparing the performance of MSMEs before and after becoming a foster partner. This research method uses descriptive research type and interviews are conducted. There are 2 assisted partners in this study, namely Wingko "O" and Anjani. The results showed that the form of the Partnership Program of PT. Telkom Witel Semarang activities carried out, namely capital loan assistance, then training activities and seminars as well as exhibition activities organized by Telkom as an annual routine activity turned out to have a positive influence on the performance of the assisted MSMEs. MSME partners fostered by Telkom Witel Semarang have improved performance on indicators of increasing business capital, conducting product innovation, organizational development, marketing through social media or e-commerce, participating in exhibitions to establish relationships, training in product use, increasing product sales turnover, developing business premises, and develop new marketsKeywords:CSR; performance improvement. Abstrak: PT. Telkom merupakan salah satu perusahaan BUMN berusaha membangun kepercayaan dengan menggunakan strategi pengembangan program-program CSR. Telkom juga telah berpikir untuk tidak lagi bekerja hanya semata-mata untuk mendapatkan keuntungan yang sebesar-besarnya, tetapi lebih cenderung mengarah kepada pembangunan keberlanjutan usaha jangka panjang serta memberdayakan masyarakat (community development). Berdasarkan wawancara dengan staff Unit CDC PT. Telkom Witel Semarang hasil evaluasi UMKM Andjani dan Wingko “O” pada laporan status laporan angsuran pengembalian dana pinjaman Program Kemitraan Telkom Witel Semarang termasuk ke dalam kategori lancar. Namun, hal ini kurang bisa menggambarkan kinerja mitra binaan ini mengalami perkembangan atau peningkatan. Pendapat ini diperkuat oleh pernyataan (Tambunan, 2012) mengenai perkembangan usaha yang dipengaruhi oleh modal, pemasaran, bahan baku, tenaga kerja, teknologi, biaya transportasi, energi yang tinggi, komunikasi, dan prosedur administrasi. Penelitian ini bertujuan untuk menganalisis sampai sejauh mana pelaksanaan CSR Program Kemitraan PT. Telkom dengan membandingkan kinerja UMKM sebelum dan sesudah menjadi mitra binaan. Metode penelitian ini menggunakan tipe penelitian deskriptif dan dilakukan wawancara. Terdapat 2 mitra binaan pada penelitian ini yaitu Wingko “O” dan Anjani. Hasil penelitian menunjukan bentuk Program Kemitraan PT. Telkom Witel Semarang kegiatan yang dilaksanakan yaitu bantuan pinjaman modal, kemudian kegiatan pelatihan dan seminar serta kegiatan pameran yang diselenggarakan oleh pihak Telkom sebagai kegiatan rutin tahunan ternyata memberikan pengaruh yang positif terhadap kinerja UMKM binaan. UMKM mitra binaan Telkom Witel Semarang mengalami peningkatan kinerja pada indikator peningkatan modal usaha, melakukan inovasi produk, pengembangan organisasi, pemasaran melalui sosial media atau e-commerce, mengikuti pameran untuk menjalin relasi, pelatihan penggunaan produk, peningkatan omzet penjualan produk, pengembangan tempat usaha, serta mengembangkan pasar baru.Kata Kunci: CSR; Peningkatan Kinerja UMKM